Methodics of Stages Musical Pedagogical Competence of Future Kindergarten Teacher and Musical Tutor Formation - Regina Savchenko (Pedagogical Discourse, 2013)
The article deals with the problem of importance of musical pedagogical competence of future kindergarten teacher and musical tutor. It also suggests the main stages formation: problem-cognitive, analytical and evaluative, projectable-creative. It reveals the problem of subjective interaction of the teachers and students in the process of future kindergarten teacher and musical tutor. Active positson of the participants of this process is defined to the methods of its successful development. It also suggests the blocks methods of formation musical pedagogical competence of future pedagogues. The blocks methods are offered on each level: presentation, algorithmically-search, inventively-search.